DECLINING FARMS AS AN EXAMPLE OF RECESIVE PROCESSES IN ECONOMY OF NATURALLY VALUABLE AREAS OF THE KRAKOW-CZĘSTOCHOWA UPLAND - Kamila Musial (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The aim of the work is to assess selected environmental and organizational aspects, as well as the level of changes occurring in farms, and therefore in agriculture in the Kraków-Częstochowa Upland. The survey-based research was carried out in 2023. The paper presents state of advancement of selected aspects of the deagrarianisation and deanimalisation processes in the area of 44 communes in the Lesser Poland and Silesian voivodeships. When dividing into two so-called macro-categories, as groups B-C (retarding farms) and C-D (degressive farms), the results indicate predominance of entities from the latter group (65%). This confirms the thesis that in research area there are problems of agrarian and structural changes, which also affect the environment. Especially crucial for the research are issues related to the advancement of deanimisation process, which is an abandonment of animal husbandry. It has a direct influence on development and use of production potential of permanent grasslands and also diversity of crops. The share of farms keeping cattle in all analyzed communes is only approximately 3-7%. It can therefore be concluded that this phenomenon is highly advanced in the majority of farms.